Inovasi Pembelajaran IPS Berbasis Teknologi: Systematic Literature Review - Sul Padli; Richlah Nur Majdina; Sinta Prahastini; Astria Wulandari; Sirajuddin Saleh (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to comprehensively analyze technology-based innovations in Social Studies learning through a Systematic Literature Review (SLR) approach. The research employed an SLR design based on the PRISMA guidelines, involving the processes of identification, selection, and synthesis of scientific articles published between 2020 and 2025. Data sources were obtained from relevant SINTA-indexed journals and analyzed using qualitative content analysis techniques. The findings reveal that technology-based innovations in Social Studies learning encompass various approaches, including blended learning, project-based learning, and the use of interactive media, Learning Management Systems (LMS), and artificial intelligence. The results also indicate that technology has a positive impact on student engagement, digital literacy, and critical thinking skills. This study contributes theoretically by strengthening the integration of the TPACK framework in Social Studies learning and practically by providing recommendations for educators and policymakers in developing innovative and adaptive technology-based learning. The limitation of this study lies in the SLR approach, which depends on the quality of the literature analyzed. Future research is recommended to examine the empirical implementation of technology in Social Studies learning through qualitative or mixed methods approaches.